2022
DOI: 10.1371/journal.ppat.1010160
|View full text |Cite
|
Sign up to set email alerts
|

ApoA-I mimetics reduce systemic and gut inflammation in chronic treated HIV

Abstract: Novel therapeutic strategies are needed to attenuate increased systemic and gut inflammation that contribute to morbidity and mortality in chronic HIV infection despite potent antiretroviral therapy (ART). The goal of this study is to use preclinical models of chronic treated HIV to determine whether the antioxidant and anti-inflammatory apoA-I mimetic peptides 6F and 4F attenuate systemic and gut inflammation in chronic HIV. We used two humanized murine models of HIV infection and gut explants from 10 uninfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 85 publications
(258 reference statements)
1
12
0
Order By: Relevance
“…1a). Similar to our prior data that potent ART effectively suppressed HIV-1 replication in NSG BLT mice [6], all HIV + ART + NSG BLT mice had suppressed plasma viremia after 4 weeks of potent ART (data not shown). NSG BLT HIV + ART + mice had increased levels of the cytokines human (h) IL-1β (Fig.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…1a). Similar to our prior data that potent ART effectively suppressed HIV-1 replication in NSG BLT mice [6], all HIV + ART + NSG BLT mice had suppressed plasma viremia after 4 weeks of potent ART (data not shown). NSG BLT HIV + ART + mice had increased levels of the cytokines human (h) IL-1β (Fig.…”
supporting
confidence: 90%
“…Three groups were used: uninfected (group A: HIV − , n = 5), infected and on ART (group B: HIV + ART + , n = 12), and infected on ART and MitoQ (group C: HIV + ART + MitoQ + , n = 10). Brain human and murine cytokines and chemokines were determined using Luminex immunoassays according to the manufacturer's instructions (R&D Systems, Minneapolis, MN, USA) and as described previously [6]. The Kruskal–Wallis test or the Mann–Whitney compared different groups.…”
mentioning
confidence: 99%
“…Kelesidis and colleagues [ 49 ■ , 50 ■ , 51 ■ ] used two humanized mouse models of HIV infection, as well as gut explants from ten uninfected and ten HIV-infected men without evident morbidity to study the chronic inflammatory response in mice and humans on ART with no detectable HIV in blood. The mice were either infected with HIV or not, either treated with ART to reduce viral load to undetectable levels in blood or the mice did not receive ART, and either received a concentrate of transgenic tomatoes expressing the 6F peptide (Tg6F) that was added to their chow or they received a control transgenic tomato concentrate without the 6F peptide.…”
Section: Gut-derived Lipopolysaccharide Oxidized Lipids and Apoa-i Mi...mentioning
confidence: 99%
“…Daskou et al . [ 51 ■ ] also found that HIV infected humanized mice on ART and the control transgenic tomato concentrate had higher gut tissue cytokine levels (TNF-α and IL-6) and chemokines (CX3CL1) that are products of a disintegrin metalloprotease 17 (ADAM17) sheddase activity compared to HIV infected humanized mice on ART and Tg6F. ADAM17 is an inflammation-inducible enzyme that is responsible for the protease-driven shedding of TNF-α, CX3CL1 and plasma soluble CD163 (sCD163).…”
Section: Gut-derived Lipopolysaccharide Oxidized Lipids and Apoa-i Mi...mentioning
confidence: 99%
See 1 more Smart Citation